The Impact on Birth Outcomes of Sonographic Fetal Weight Estimation in Neonatal Macrosomia - Sgayer, Inshirah; Nskovica, Karina; Murkhovskyi, Iuliia; Shqara, Raneen Abu; Bilyk, Artyom; Lowenstein, Lior; Wolf, Maya Frank (American Journal of Perinatology, 2024)
Objective Our objective was to examine the association between sonographic estimated fetal weight (EFW) and obstetrical and neonatal outcomes in women with neonatal macrosomia.Study Design This study, conducted at a tertiary university-affiliated hospital from 2017 to 2021, compared obstetrical and neonatal outcomes between two groups of women who delivered macrosomic newborns (actual birth weight ≥ 4,000 g): (1) those with EFW ≥ 3,800 g (suspected impending macrosomia) and (2) those with EFW < 3,800 g (unsuspected impending macrosomia).Results During the study period, 854 women with neonatal macrosomia attempted vaginal delivery. Only 9.2% had a sonographic EFW ≥ 4,000 g. Among women with EFW ≥3,800 g (n = 317) compared with EFW < 3,800 g (n = 537), the cesarean delivery (CD) rate was higher (17.0 vs. 10.5%, p = 0.004) and the operative delivery rate was lower (3.2 vs. 0.6%, p = 0.015). Among primiparous women, the CD rate was higher among those with EFW ≥ 3,800 versus <3,800 g (37.3 vs. 23.2%, p = 0.033). EFW ≥3,800 g was associated with CD, regardless of predelivery body mass index, parity, diabetes mellitus, maximal fetal weight at previous deliveries, actual birth weight, and labor induction (p = 0.014). EFW ≥3,800 g and diabetes mellitus were independent predictors of CD. Among women with EFW ≥3,800 g and diabetes mellitus, the risk of CD was double that of those without diabetes and with EFW ≥ 3,800 g (31.4% vs. 15.2%, p = 0.02), although their actual birth weights were similar. Obstetrical and neonatal outcomes were similar between those with sonographic EFW ≥3,800 and < 3,800 g.Conclusion Larger EFW increased CD risk among pregnancies with actual neonatal macrosomia. Antenatally suspected macrosomia might alter labor management due to concerns for potential complications, especially when associated with primiparity, diabetes mellitus, or maternal obesity. The increase in the CD rate did not show an association with improved maternal and neonatal outcomes.Key Points
Keywords: sonographic estimated fetal weight; macrosomic newborns; cesarean delivery; primiparity; diabetes mellitus; maternal obesity